ANALISIS PENGARUH HEDONISME, TINGKAT PENDAPATAN DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN GEN Z DI KOTA BATAM - Glaedisya (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study analyzes the influence of hedonism, income level, and financial literacy on the financial behavior of Generation Z women in Batam City. The research is based on socio-economic phenomena where many young women face financial mismanagement due to consumerist lifestyles, limited income, and poor financial understanding. A quantitative approach was used, with data collected through questionnaires distributed to 100 Gen Z female employees working in the private sector in Batam. Multiple linear regression analysis was employed to examine the data. The results show that hedonism has a significant negative effect on financial behavior—higher hedonism leads to poorer financial behavior. In contrast, income level and financial literacy have a significant positive impact, indicating that individuals with better income and financial knowledge tend to exhibit wiser financial behavior. Simultaneously, all three variables significantly influence financial behavior. This suggests the importance of promoting financial literacy and effective income management to build healthier financial habits, particularly in overcoming consumerism in the digital era. These findings can be used as a reference for developing financial education policies and as practical guidance for Gen Z women to improve their financial well-being in the long term.